Expression of immune-modulatory molecules HLA-G and HLA-E by tumor cells in glioblastomas: an unexpected prognostic significance? - Kren, Leos; Slaby, Ondrej; Muckova, Katarina; Lzicarova, Eva; Sova, Marek; Vybihal, Vaclav; Svoboda, Tomas; Fadrus, Pavel; Lakomy, Radek; Vanhara, Petr; Krenova, Zdenka; Sterba, Jaroslav; et al. (Neuropathology, 2011)
The role of nonclassical human leukocyte antigens G and E (HLA-G and HLA-E) was originally thought to be restricted to the protection of the fetus from a maternal allorecognition. Now it is known that HLA-G and HLA-E exert multiple immunoregulatory functions. A prognostic significance of the expression of HLA-G and HLA-E by neoplastic cells in glioblastoma is not well characterized. In this study, we evaluated the expression of HLA-G and HLA-E by neoplastic cells in 39 cases of glioblastoma. We found the production of HLA-G and HLA in a majority of cases. There was an unexpected positive correlation between the expression of HLA-E and length of survival. We speculate that the expression of this molecule by neoplastic cells may represent a coincidental selective pro-host advantage related to better response to subsequent therapeutic modalities. Mechanisms of glioblastoma cell pathophysiology and mechanisms of responses to therapeutic interventions in respect to the expression of these molecules deserves further study.
Keywords: MHC antigeny I. třídy; Tissue Array Analysis; HLA-G Antigens; Cell Line, Tumor; Immunohistochemistry; nádory mozku; lidé; čipová analýza tkání; imunohistochemie; glioblastom; prognóza; Glioblastoma; HLA-E Antigens; nádorové biomarkery; Brain Neoplasms; HLA-G antigeny; Prognosis; HLA antigeny; Biomarkers, Tumor; antigeny HLA-E; HLA Antigens; Histocompatibility Antigens Class I; nádorové buněčné linie; Humans